2007
DOI: 10.1093/eurheartj/ehm176
|View full text |Cite
|
Sign up to set email alerts
|

Detection of recent myocardial ischaemia by molecular imaging of P-selectin with targeted contrast echocardiography

Abstract: Molecular imaging of P-selectin with targeted MCE can identify the presence of recently ischaemic myocardium in the absence of necrosis and after resolution of hypoperfusion and post-ischaemic stunning. This technique can potentially provide a method for risk stratifying patients with acute chest pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
94
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(97 citation statements)
references
References 20 publications
2
94
0
1
Order By: Relevance
“…Up-regulation of endothelial adhesion molecule 1 (VCAM-1) and intercellular cell adhesion molecule 1 (ICAM-1) is detected on endothelium of atherosclerotic plaques [26]. Selectins are also upregulated in inflammation [27].…”
Section: Molecular Imagingmentioning
confidence: 99%
“…Up-regulation of endothelial adhesion molecule 1 (VCAM-1) and intercellular cell adhesion molecule 1 (ICAM-1) is detected on endothelium of atherosclerotic plaques [26]. Selectins are also upregulated in inflammation [27].…”
Section: Molecular Imagingmentioning
confidence: 99%
“…al. [33] have recently shown that ischemic myocardium can be visualized using contrast echocardiography targeted to P-selectin. It is possible that these techniques may be extended to permit targeted delivery of stem cells.…”
Section: Targeted Imagingmentioning
confidence: 99%
“…However, methodologic problems remain. The agents used were based either on P-selectin-avid antibodies (10,11) or on synthetic analogs of Sialyl Lewis X (SLe X ), the natural ligand of P-selectin (7,8,10). Although the antibody-based agents generally yield good imaging results (9,11), the production of these tracers is expensive and time-consuming.…”
mentioning
confidence: 99%
“…Although the antibody-based agents generally yield good imaging results (9,11), the production of these tracers is expensive and time-consuming. The clinical potential of SLe X analogs, on the other hand, is limited by their poor imaging properties (7,8,10).…”
mentioning
confidence: 99%
See 1 more Smart Citation